The Intergenerational Effects of Relocation Policies on Indigenous Families - Walls, Melissa L. (2012)
This research utilizes life-course perspective concepts of linked lives and historical time and place to examine the multigenerational effects of relocation experiences on Indigenous families. Data were collected from a longitudinal study currently underway on four American Indian reservations in the Northern Midwest and four Canadian First Nation reserves where residents share a common Indigenous cultural heritage. This paper includes information from 507 10 – 12 year old Indigenous youth and their biological mothers who participated in the study. Results of path analysis revealed significant direct and indirect effects whereby grandparent-generation (G1) participation in government relocation programs negatively impacts not only G1 well being, but also ripples out to affect subsequent generations.